Applications of discrete geometry and mathematical morphology first international workshop, WADGMM 2010, Istanbul, Turkey, August 22, 2010, revised selected papers - Montanvert, Annick; Soille, Pierre; Köthe, Ullrich (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the first Workshop on Applications of Discrete Geometry and Mathematical Morphology, WADGMM 2010, held at the International Conference on Pattern Recognition in Istanbul, Turkey, in August 2010. The 11 revised full papers presented were carefully reviewed and selected from 25 submissions. The book was specifically designed to promote interchange and collaboration between experts in discrete geometry/mathematical morphology and potential users of these methods from other fields of image analysis and pattern recognition.